Primary versus secondary antiemetic prophylaxis with NK1 receptor antagonists in patients affected by gastrointestinal malignancies and treated with a doublet or triplet combination regimen including oxaliplatin and/or irinotecan plus fluoropyrimidines: A propensity score matched analysis - Parisi, Alessandro; Giampieri, Riccardo; Mammarella, Alex; Felicetti, Cristiano; Salvatore, Lisa; Bensi, Maria; Maratta, Maria Grazia; Strippoli, Antonia; Filippi, Roberto; Satolli, Maria Antonietta; Petrillo, Angelica; Daniele, Bruno; et al. (Frontiers in Oncology, 2022)
Aim: This study aimed at investigating the impact of primary compared to secondary chemotherapy-induced nausea and vomiting (CINV) prophylaxis with NK1 receptor antagonists (RA) in patients affected by gastrointestinal malignancies and treated with doublet or triplet-chemotherapy regimens. Study design and Methods: Clinical data of patients affected by gastrointestinal malignancies, treated with a doublet or triplet regimen as neo/adjuvant or advanced-line treatment, and who received NK1-RA as primary (from the first cycle of treatment) or secondary (after the onset of CINV with a previous regimen with 5HT3-RA and dexamethasone) prophylaxis for CINV, were retrospectively collected in an observational study involving 16 Italian centres. A propensity score matching was performed by taking into account: sex (male vs female), age (< vs ≥ 70 years old), overweight (BMI < vs ≥ 25), underweight (BMI < vs ≥ 19), disease spread (early vs advanced/metastatic), tumor type, type of NK1-RA used as primary/secondary prophylaxis (netupitant-palonosetron vs fosaprepitant/aprepitant), concomitant use of opioids (yes vs no), concomitant use of antidepressant/antipsychotic drugs (yes vs no), ECOG PS at the start of NK1-RA treatment (0 vs 1-2), intensity of chemotherapy regimen (doublet vs triplet). Results: Among 409 patients, 284 (69%) and 125 (31%) were treated with NK1-RA as primary and secondary antiemetic prophylaxis, respectively. Primary NK1-RA use was not associated with higher rates of protection from emesis regardless the emesis phase (acute phase, p=0.34; delayed phase, p=0.14; overall phase, p=0.80). Nevertheless, a lower rate of relevant nausea (p=0.02) and need for rescue antiemetic therapy (p=0.000007) in the overall phase was found in primary NK1-RA users. Furthermore, a higher rate of both complete antiemetic response (p=0.00001) and complete antiemetic protection (p=0.00007) in the overall phase, was more frequently observed in primary NK1-RA users. Finally, chemotherapy delays (p=0.000009) and chemotherapy dose reductions (p=0.0000006) were less frequently observed in primary NK1-RA users. Conclusion: In patients affected by gastrointestinal malignancies, a primary CINV prophylaxis with NK1-RA, 5HT3-RA and dexamethasone might be appropriate, particularly in those situations at higher risk of emesis and in which it is important to avoid dose delays and/or dose reductions, keeping a proper dose intensity of chemotherapy drugs.